The Factors that Influence the User Intention to Use SI APIK Application by UMKM in Kabupaten Garut Using UTAUT2 Model - Susilawati, Wati; Adisti, Tirania; Turipanam Alamanda, Dini; Noura, Athiya (KnE Social Sciences, 2023)
A lack of knowledge about the correct procedures for financial recording in UMKM can cause the performance problem for a company. Thus, Bank Indonesia together with the Indonesian Accounting Association (IAI) created SI APIK (Sistem Informasi Aplikasi Pencatatan Informasi Keuangan) to help expand business capacity and access to capital for UMKM in Indonesia. This study analyzes the factors that influence the user intention to use the SI APIK application by UMKM in Kabupaten Garut using the UTAUT2 model. The framework is based on research from Eneizan et al. who stated that business expectations, social influences, performance expectations, hedonic motivation, facilitation conditions, price values, and habit variables affect behavioral intentions. The analytical method used in this study is a quantitative method with a descriptive method. Data were collected by questionnaires to 100 respondents using the accidental sampling technique. The collected data was then analyzed using structural equation modeling (SEM). The results of the study revealed that the variables of performance expectancy, price value, and habit have a positive and significant effect on behavioral intention. While the variables effort expectancy, social influence, and facilitating conditions have no significant effect on behavioral intention. Keywords: behavioral intention, PLS-SEM, UTAUT2